PENGOLAHAN JAHE INSTAN SEBAGAI MINUMAN HERBAL DI MASA PANDEMIK COVID - 19 - SAFRIN EDY; ANTASALAM AJO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The corona outbreak is still a disease that cannot be predicted when it will stop. There are many things that can be done. Starting from eating nutritious food to maintaining stamina with exercise and taking herbal medicines so that the body's immune system remains optimal during the Covid pandemic, one of which is ginger. Kaongke-Ongkea Village has the potential for ginger plants to be developed as instant jehe production as herbal drinks to maintain endurance and body warmth. The purpose of this community service activity is to provide information and knowledge about instant ginger products that can increase family economic income during a pandemic and provide skills in the process of making instant ginger products with innovative new flavors to be commercialized.The method of activities that will be applied to achieve the goals of community service is the method of lectures, discussions and demonstrations directly in the field which is based on an initial evaluation to find out the knowledge and skills of the target group about processing instant ginger as an herbal drink. Based on the results of the training activities that have been carried out, it can be concluded that instant ginger processing service activities can provide information and knowledge about instant ginger products can increase family economic income during a pandemic if it is carried out properly and service activities for instant ginger processing can provide skills in the process of making instant ginger products with innovative new flavors for commercialization